2012
DOI: 10.1002/pmj.21281
|View full text |Cite
|
Sign up to set email alerts
|

Project Management for Development in Africa: Why Projects are Failing and What Can be Done about It

Abstract: This article discusses international development (ID) projects and project management problems within ID in Africa and suggests they may fall into one or more of four main traps: the one-size-fits-all technical trap, the accountability-for-results trap, the lack-of-project-management-capacity trap, and the cultural trap. It then proposes an agenda for action to help ID move away from the prevailing one-size-fits-all project management approach; to refocus project management for ID on managing objectives for lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
179
1
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(193 citation statements)
references
References 33 publications
1
179
1
12
Order By: Relevance
“…We need to ascertain what is really taking place. Thus this special issue is not about the contribution that project management could make to Africa (Ika, 2012) or what good project governance or management should be in that continent (e.g., Marnewick & Labuschagne, 2011). Instead, it is about what project management means in Africa, how project management is practiced in Africa, and what actually does work or does not work in that context (e.g., Muriithi & Crawford, 2003).…”
Section: The Contribution Of This Special Issuementioning
confidence: 97%
See 1 more Smart Citation
“…We need to ascertain what is really taking place. Thus this special issue is not about the contribution that project management could make to Africa (Ika, 2012) or what good project governance or management should be in that continent (e.g., Marnewick & Labuschagne, 2011). Instead, it is about what project management means in Africa, how project management is practiced in Africa, and what actually does work or does not work in that context (e.g., Muriithi & Crawford, 2003).…”
Section: The Contribution Of This Special Issuementioning
confidence: 97%
“…During the same period, Africa has relied increasingly on project management to achieve its development goals. Yet while Africa is replete with brilliant, impeccable, colorful, and well-written development visions, policies, programs, plans, and projects, many observers point out that abandoned, failed, or poor performing projects are paramount in Africa and that they have even thwarted its development (Eneh, 2009;Ika, 2012).…”
Section: Why Africa Needs Good Projectmentioning
confidence: 98%
“…Ika et' al (2012) carried out a regression analysis which shows that there was a statistically significant and positive relationship between each of the five Critical Success Factors and project success. The five critical success factors include monitoring, coordination, design, training and Institutional environment.…”
Section: Relationship Between Mande and Project Successmentioning
confidence: 99%
“…Most frequently projects are considered failures when they fail to meet their targeted cost, time, or scope. However, Ika (2012) demonstrated that projects may be completed within their targeted time, cost and scope criteria but still be classified as failures. Therefore, it becomes necessary to consider failure beyond these criteria and include targets such as the aspiration of stakeholders, the benefits accruing to society or project organisation among criteria for determining project failure.…”
Section: A Perspective Based Understanding Of Project Success and Faimentioning
confidence: 99%